Capacity Building of MSME Actors through Online Business Innovation Training and the Utilization of Digital Media - Ningsih, Murni; Sangadji, Fajriyani; Septa, Giar (Siddiq Institute, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving economic growth but often face challenges in marketing and business management in the digital era. This study aims to enhance the capacity of MSME actors through training in online business innovation and the utilization of digital media. The methods employed include a participatory approach, practical training, and intensive mentoring for MSME actors in the target area. The training materials cover digital marketing strategies, the use of social media as a promotional platform, and the optimization of marketplaces to increase sales. The results of the study indicate that after participating in the training, MSME actors experienced improved skills in creating creative content, utilizing digital marketing features, and managing online stores. Additionally, there was an average sales increase of 35% within three months post-training. This study concludes that training in online business innovation and the utilization of digital media significantly contributes to strengthening the competitiveness of MSMEs in the digital era.Keyword: MSMEs, online business innovation, digital, digital marketing